Language as hope - Silva, Daniel N.; Lee, Jerry Won (Cambridge University Press, 2024)
Although it feels like we live in a time of seeming hopelessness, this pioneering book illustrates what language can teach us about the practice, logic, and feasibility of hope in the twenty-ﬁrst century. Silva and Lee highlight how people living in Brazilian urban peripheries, who have grown accustomed to unrelenting prejudice and violence on an everyday basis, use language to survive and imagine futures that are worth aspiring to. In so doing, this book foregrounds how language becomes a matter of survival for these communities. It provides a thorough theorization of how language can produce conditions of hope, moving away from the idea of language merely as a tool of communication and toward something that can meaningfully impact social realities. Innovative and engaging, it is essential reading for researchers and students in applied linguistics, sociolinguistics and linguistic anthropology. This title is also available as open access on Cambridge Core.